Trimetallic nanoparticles in anaerobic digestion process for biogas production - Jadhav Pramod, Chandrakant (2023)
Nanoparticles (NPs) have emerged as an amazing class of materials with a broad spectrum of examples with at least one dimension in the range of 1 to 100 nm. Metallic NPs can be produced with outstanding magnetic, electrical, optical, mechanical, and catalytic properties that are substantially different from their bulk counterparts. Nowadays, NPs are used in the anaerobic digestion (AD) process for enhancing biogas yield. However, NPs activity and electron exchange capacity depend on their interaction and inhibition effects on microbes in the AD process. Currently, to increase NPs activity and functionality, various organic and inorganic synthesis methods have been applied for the last two decades. In the same way, the co-precipitation method was used to prepare less hazardous, highly active NPs for microbes-to-microbes interaction compared to other methods. The present study focused on the trimetallic nanoparticles (TMNPs) made of iron (Fe), nickel (Ni), zinc (Zn), copper (Cu) and cobalt (Co) are considered the most effective materials for biomass conversion through the AD process. This study used palm oil mill effluent (POME) as biomass, and different concentrations of active TMNPs were used for biogas production. Fe-Ni-Zn, Fe-Co-Cu and Fe-Co-Zn TMNPs interact with microbes and help to degrade biomass under anaerobic conditions. At 10 mg/L, 20 mg/L, 30 mg/L, 40 mg/L and 50 mg/L TMNPs and POME-based mesophilic (37±1°C) AD was investigated for biogas production. Secondly, 20 mg/L Fe-Co-Zn TMNPs at pH 7.0 increased biogas production by 60.11% compared to the control AD. This work aims to determine ideal conditions for higher biogas with lesser TMNPs using response surface methodology (RSM). As a result, the mesophilic condition (250C -350C) of the POME-based AD process increased by 85% biogas production compared to the blank AD process (p < 0.05). However, The AD process has some limitations (TMNPs toxicity, antibacterial effects, less microbes interaction) and needs to focus on organic waste-to-energy production. Nevertheless, the biogas yield increased to 85% from moderate AD conditions with minimal Fe-Co-Zn TMNPs addition. Finally, other future perspectives worth investigating are reported to understand the microbial interaction and toxicity of TMNPs in deep for higher biogas production with lesser TMNPs concentration.